PROBLEM ANALYSIS OF THE DEVELOPMENT OF PALM OIL PLANTATIONS PT. AGRO SYNERGY NUSANTARA KEBUN UJUNG LAMIE, NAGAN RAYA REGENCY - Suhardi Simbolon; Aswin Nasution (CV. Radja Publika, 2023)
Oil palm is a plantation crop that produces vegetable oil while increasing the economy of people in developing countries, including in Indonesia, including PT. ASN is located in Nagan Raya district, but various problems are faced in developing the oil palm plantation. This research was conducted with the aim of looking at the various problems faced by PT. ASN Nagan Raya district in the development of oil palm plantations, using 11 staff respondents and employees of plantation companies, the results of this study indicate that the problem of developing PT. ASN at Ujung Lamie Nagan Raya Gardens are low productivity, low human resources, unstable finances, lack of fertilization, poor road infrastructure, lack of discipline, Inadequate facilities, many vacant areas, attacks by pigs and porcupines during planting, lack of harvesting bridges, high fertilizer prices and educational factors. Solving these various problems can develop plantations in accordance with the company's business objectives.